Evaluasi Kesintasan dan Pertumbuhan Beberapa Jenis Pohon Lokal di Area Restorasi Cagar Biosfer Cibodas - Handayani, Aisyah; Lailaty, Intani Quarta; Astutik, Sri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
One of the threats faced with Cibodas Biosphere Reserve area is the changes of forest area into plantation. Various efforts were made by Gunung Gede Pangrango National Park (TNGP) management to restore the area to its original function. One of the efforts is planting trees in the ex-plantation area that has been abandoned by the farmers. In 2016, Cibodas Botanics Garden was collaborated with TNGP to plant native trees species that had potency of high carbon sequestration. Six hundreds seedlings from 12 native trees species were planted ie, Altingia excelsa Noronha, Castanopsis argentea (Blume) A.DC., Castanopsis javanica (Blume) A.DC., Castanopsis tunggurut (Blume) A.DC, Dacrycarpus imbricatus (Blume) de Laub., Euonymus indicus B. Heyne ex Wall., Lithocarpus indutus (Blume) Rehder, Magnolia blumei Prantl, Persea rimosa Zoll. ex Meisn., Syzygium acuminatissimum (Blume) DC., Sloanea sigun (Blume) K. Schum., and Schima wallichii Choisy. The observations of evaluation done by January, February and July 2016. Parameters were observed are plant height, root collar diameter and crown width. Then, the data were analyzed by RGR (Relative Growth Rate) and RPI (Relative Performance Index). The results of observation during six months after planting shown that the average survival rate was 60.56%, with the largest survival rates were Altingia excelsa and Castanopsis javanica (80%). Castanopsis tunggurut was the lowest survival rate than the other plants (33,33%). The best growth rate is shown by Schima wallichii. In this case, obstructed plant growth is caused by the high density of weeds and shrubs so that seedlings are less exposed to sunlight and nutritional deficiencies, and also the damage that caused by humans, especially for Castanopsis tunggurut and Sloanea sigun.